Safety and Efficacy of Adjunctive Therapy With Artesunate in the Treatment of Severe Malaria: A Systematic Review and Meta-Analysis - Zou, Yuanyuan; Tuo, Fei; Zhang, Zhiqi; Guo, Jiawen; Yuan, Yueming; Zhang, Hongying; Xu, Zhiyong; Pan, Ziyi; Tang, Yexiao; Deng, Changsheng; Julie, Nadia; Wu, Wanting; et al. (Frontiers in Pharmacology, 2020)
Objective: The purpose of this meta-analysis of longitudinal studies is to determine the safety and efficacy and artesunate combined with other forms of adjuvant therapies for severe malaria. Methods: Following the Prisma guidelines, we searched multiple databases with the search terms: “artesunate” and “adjunctive therapy” and “severe malaria” in July 2020. If the search yielded either a prospective cohort study or a study reporting a randomized controlled trial (RCT), the study was included in this meta-analysis. The random-effects model was used to calculate the combined incidence rate and relative risk or risk difference. Results: This meta-analysis included nine longitudinal studies with 725 participants. We found that the mortality rates in the artesunate monotherapy group and the artesunate+adjuvant therapy group are similar (RD= 0.02, 95%CI: 0.02-0.06). Artesunate, combined with adjuvant therapy, did not significantly improve the renal protection rate of patients with severe malaria (RD= 0.04, 95%CI: 0.03-0.11). The incidence of adverse reactions in the artesunate monotherapy group and the artesunate+adjuvant therapy group was also similar. Conclusions: No significant differences in safety and efficacy were observed between the artesunate monotherapy group and the artesunate+adjuvant therapy group. Higher quality and rigorously designed randomized controlled studies are needed to validate our findings.